Prince For A Day - Mariam Salam (Lahore Sang-e-Meel Publications, 2002)
A fantasy for children-about people in high places and low places; and the human hearts which are the same in all places.
Include Sketches bad Glossary.
Keywords: Stories -- Story - Children -- English Short Stories